REVIEW OF PAST AND PRESENT EBOLA HEMORRHAGIC FEVER OUTBREAKS IN THE DEMOCRATIC REPUBLIC OF CONGO 1976 -2014 - Kasangye, Aurelie Kasangye; Muloye, Guy Mutangala; Avevor, Patrick Mawupemor; Shixue, Li (African Journal of Infectious Diseases (AJID), 2015)
Background: Ebola Hemorrhagic Fever (EHF) has become well known all over the world, especially following the West African outbreak in Guinea, Sierra Leone and Liberia (December 2013). The Ebola virus was first discovered in the Democratic Republic of Congo (DRC), an African country that has continued to register Ebola outbreaks. This study aims to summarize old and new experiences of Ebola in the DRC, in order to propose strategies for better prevention. Materials and Methods: Information was taken from databases such as PubMed and Cochrane library. A total of eleven full text and three abstracts were identified for the data extraction. Results: Since its discovery in the DRC, there have been seven Ebola outbreaks, accounting for a total of 1032 cases and 795 deaths. The presence of Non-Human Primates, also considered as the natural reservoir and susceptible host of Ebola virus, can be one major factor that has contributed to the increased number of Ebola outbreaks and cases in the Equatorial region. The existence of rumors and legends related to Ebola in DRC obscure the the viral nature of the disease, and lead to difficulty for health workers, to easily accomplish their tasks. Conclusion :It is important ,to scale up community education campaigns designed to give more details on the viral nature of the EHF, establish national agencies and institutions specialized in controlling hunting in the Equatorial region, for better prevention, since there is not yet a specific drug or vaccine to the Ebola Virus.